First Aid Intervention Method to Enhance Knowledge Among Middle School Students - Sitti Syabariyah; Nuni Apriani; Fannisya Tria Gunawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Injuries are common in school environments, particularly among middle school students, who are more susceptible to accidents due to their active physical engagement and limited knowledge of first aid. This community service program aims to enhance students’ understanding of wound care as a first aid intervention through interactive lectures, discussions, and simulations. This program seeks to improve students' knowledge and contribute to advancements in school health, especially by equipping adolescents to administer first aid. By directly educating students, the program empowers them to act as first responders, providing immediate assistance until professional medical help is available. Pre- and post-test evaluations showed a significant increase in knowledge scores of 27.31 points. This method can serve as a model for implementing health education in schools.